2022
DOI: 10.1002/anie.202202744
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Electrochemical Microscopy for the Elucidation of the Local Ionic and Electronic Properties of the Solid Electrolyte Interphase in Li‐Ion Batteries

Abstract: The solid‐electrolyte interphase (SEI) plays a key role in the stability of lithium‐ion batteries as the SEI prevents the continuous degradation of the electrolyte at the anode. The SEI acts as an insulating layer for electron transfer, still allowing the ionic flux through the layer. We combine the feedback and multi‐frequency alternating‐current modes of scanning electrochemical microscopy (SECM) for the first time to assess quantitatively the local electronic and ionic properties of the SEI varying the SEI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 50 publications
(79 reference statements)
0
25
0
1
Order By: Relevance
“…168 Recently, Santos et al combined feedback and multifrequency alternating-current modes of scanning electrochemical microscopy (SECM) to evaluate quantitatively the local and in situ electronic and ionic properties of SEI in LIBs for the first time, respectively. 169 The method has potential in calculating the critical parameters of SEI, such as resistivity and dielectric permittivity. In summary, although EIS is a proven technique in characterizing the electrical properties of SEI, the thorny issue is to quantitatively assess the thickness evolution of the SEI during battery aging by monitoring impedance change.…”
Section: Platingmentioning
confidence: 99%
“…168 Recently, Santos et al combined feedback and multifrequency alternating-current modes of scanning electrochemical microscopy (SECM) to evaluate quantitatively the local and in situ electronic and ionic properties of SEI in LIBs for the first time, respectively. 169 The method has potential in calculating the critical parameters of SEI, such as resistivity and dielectric permittivity. In summary, although EIS is a proven technique in characterizing the electrical properties of SEI, the thorny issue is to quantitatively assess the thickness evolution of the SEI during battery aging by monitoring impedance change.…”
Section: Platingmentioning
confidence: 99%
“…These gap areas with poor contact may lead to the electrode surface being prone to be the sites of the electrolyte decomposition, Li deposition, capacity loss, gas generation, and other undesirable reactions, which may greatly affect the safety of LIBs. [75][76][77][78] Therefore, ultrasonic scanning images is an important "non-destructive testing" technology to study the interface wetting and stable state of electrolyte during battery aging. At the same time, it has d,e) Comparison of the Δλ B changes with dQ/dV from sixth to the tenth cycle for micro-Si and nano-Si electrodes, respectively.…”
Section: Judgment Of the Phase Interface Compatibility And Stabilitymentioning
confidence: 99%
“…In this review, the factors that may cause batteries' safety problems are demonstrated from different component levels of the [78] Copyright 2022, Wiley.…”
Section: Summary and Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scanning electrochemical microscopy (SECM) and scanning ion conductance microscopy (SICM) are powerful in situ noninvasive techniques to acquire the local topography and activity imaging , of the substrates by monitoring the electron transfer or ion transport current signals, , and thus find broad applications in various emerging fields , including electrocatalysis, , single cell analysis, , corrosion, and sensing . Recently, the development of nanoelectrodes further put forward a higher desire for nanoscale SECM/SICM techniques with high temporal and spatial resolutions , toward revealing the local structure–activity relationship at the catalysis surface, , uncovering the dynamics of single molecules, and realizing the imaging and analysis of single living cells. , …”
mentioning
confidence: 99%